Novel oxazepinedione-derived symmetric dimers: synthesis and mesophase characterisation of seven-membered heterocyclic compounds. Issue 12 (25th September 2016) - Mohammad, AbdulKarim-Talaq; Srinivasa, H. T; Suresh, HariPrasad; Yeap, Guan-Yeow
ABSTRACT: The synthesis and characterisation of three sets of symmetric dimeric compounds composed of seven-membered oxazepinedione heterocyclic rings were carried out. All the dimers possess the tetradecyl- ( n = 14) alkyl side chain attached to the nitrogen atom of the oxazepinedione core. The oxazepinedione core in turn was connected with varied connecting spacers ( n = 4, 6, 8, 10 and 12). The dimers were spectroscopically characterised by FT-IR, 1 H-NMR, 13 C-NMR and elemental analysis techniques. The compounds were investigated for liquid crystalline properties using differential scanning calorimetry and polarising optical microscopy with heating assembly. The precursor imines2a–e itself started exhibiting liquid crystalline SmA/tilted hexatic mesophase. Further fusion of2a–e with maleic anhydride, succinic anhydride and phthalic anhydride gave the novel oxazepinedione-derived symmetric dimers3a–e, 4a–e and5a–e respectively. The dimers3a–e and4a–e did not exhibit any liquid crystal (LC) properties. However, the phthalic anhydride-fused oxazepinediones5a–e show monotropic nematic liquid crystalline phase. The results indicate that the formation of mesophase is dependent on the type of fused oxazepinedione ring. GRAPHICAL ABSTRACT: